"Sem medo de ser feliz na agricultura familiar": o caso do movimento de agricultores em Constantina - RS - Picolotto, Everton Lazzaretti (2006)
The social contradictions in the field are made as "fertile land" for mobilization of agent s arguers of the order and conveyers of the social transformation. The objective of this dissertation was to characterize a movement of family farmers with performance in the municipal district of Constantina-RS, being attempted, particularly, to its potential of social transformation. Based firstly on the authors' theoretical contributions like Touraine s and Castells and of the rebuilding of the path and of the specificities of the social movements in the South of Brazil took place a case study, with "successive approach" of the study object, being privileged the description of the political path, the processes of formation of the identities, the social opponents and the future projects. This movement appeared in the middle of the 80 s, as result of the crisis conjuncture that passed the local agriculture and motivated by the of basis work of the Catholic Church. Initially, the movement assumed an opposition posture to the hegemonic political forces and, for the conquest of the Union of the Rural Workers, it had engaged on the popular forces which looked for extension of the citizenship rights, public politics and democratization. The movement took initiatives of fomentation of the productive diversification, of experiences of alternative agriculture and of formation of associations of agricultural cooperation, deflagrating a resistance process to the specialized agriculture. In the first half of the 90 s, front to the neoliberal politics, it maintained the resistance tactics, and the movement assumed the identity (of resistance) of "small farmer" and it took the initiative of building a production cooperative, seeking to supply the absence of politics of the State and to increase the possibilities of the farmers' socioeconomic reproduction. Recently (starting from the second half of the 90 s), the institutional and political changes have been favoring a dialogue relationship and cooperation of the movement with some sections of the State. This new relationship with state sections made possible the significant increase of the public policy and a change in the strategy of the movement which passed to adopt a project identity (that of "family farmer"). That new condition is interpreted, for this work, as a positivist "meaning shift" from the "small agriculture" to the "family agriculture". The potential of transformation of the movement is mainly identified in the cultural renewal which socially values the way of life and the production of the family agriculture. It has been making possible the statement of this social section as one of the main agents of the agricultural production of Brazil. However, it is also verified that the new strategy promotes the secondary goal of the project of transformation of the social structure (overcoming the capitalism) and this new situation has been provoking divergences with other popular social actors which were old allies. Such divergences provoked the differentiation of the strategies of the main social movements of the field, in the South of Brazil, such as: Federation of the Workers of the Family Agriculture of the South Area (FETRAF-south) and Rural Road. The differentiation of strategies translates itself in disputes between the movements and the disputes are done presents in the conditioning of the performance of the farmers of Constantina movement.